Clinical Evaluation of Local Drug Delivery of Chlorhexidine and Ornidazole in the Treatment of Gingivitis as an Adjunct to Scaling and Root Planing - Roopalakshmi Narayanan1 , Munivenkatappa Lakshmaiah Venkatesh Prabhuji2 , Shaeesta Khaleelahmed Bhav (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Local drug delivery to gingival sulcus avoids adverse effects seen with systemic therapy andthere is very little information to substantiate the additive effect of the drugs, the current study makes anattempt in same regard.Aim: The objective of this study was to compare the local application of ornidazole and chlorhexidine gel(ClorniTM gel) as an adjunct to scaling and polishing, with scaling and polishing alone.Materials and methods: 33 patients meeting inclusion criteria were randomly allocated to treatmentgroups by computerized randomly selection method. Indices were recorded at baseline at their first visit.Supragingival and subgingival scaling and polishing was performed using hand and ultrasonic instruments.The patients were evaluated clinically by using the gingival index, plaque index and modified sulcus bleedingindex. On test side, ClorniTM gel was applied subgingivally after nonsurgical periodontal therapy. On thecontrol side, no intervention was done following subgingival scaling and polishing. Patients were recalledat 7th day for subsequent administration of gel on the same site and followed up at 21st day and 3 months tocompare the gingival condition by using the indices.Results: All subjects showed significant improvement over 3 months recall period, irrespective of test orcontrols. Statistical significance (p? 0.05) was observed at 7 days and 21 days for test group for the gingivalindex and at 21 days for the plaque index and modified sulcus bleeding index.Conclusion: The topical gel when used as an adjunct to scaling and polishing had significant results.